Impact of seasonal variability of infiltration rates on the land area required for green infrastructure implementation - Mantilla, Ivan; Flanagan, Kelsey; Muthanna, Tone Merete; Viklander, Maria (Luleå tekniska universitet, Arkitektur och vatten, 2022)
Dimensioning green infrastructure (GI) to achieve different stormwater targets (e.g., runoff volume reductions) is essential at city scale under conditions of limited resources and space. Traditional GI sizing criteria are based on the hydrology of moderate climates. However, cold climate conditions represent an additional challenge for GI design. This paper presents an assessment of the bioretention cell (BC) area required to achieve a given runoff volume reduction (RVR), accounting for seasonal variations in infiltration rates in the Swedish cities of Gothenburg, Orebro, and Kiruna. Clear seasonal differences were found in Kiruna for the areas required to achieve 80% of RVR under winter and summer conditions. However, non-significant seasonal differences were found in Orebro and Gothenburg. For an efficient BC adoption, sizing needs to be completed in the context of the precipitation for the entire year, including the effect of snowmelt, rain-on-snow, and frozen soils.